The prevalence and correlates of nicotine use disorder among bipolar patients in a Hospital Setting, Malaysia - Yee, A.H.A.; Ng, C.G.; Abd Rashid, R.; Habil, M.H. (2012)
Objective: The authors sought to determine the prevalence of nicotine use disorder, related demographic characteristic features, and associated correlates of nicotine use disorder among bipolar patients who attended inpatient and outpatient services in a university hospital setting in Malaysia. Methods: In this cross-sectional study conducted from March 2009 to September 2010, a total of 121 bipolar patients, whose diagnoses were based on the Mini International Neuropsychiatric Interview (bipolar version 5.0.0), were recruited. Their nicotine use disorders were assessed with the Mini International Neuropsychiatric Interview (plus version) and the Fagerstrom Test for Nicotine Dependence. The associated correlates of nicotine use disorder were assessed with the Addiction Severity Index-Lite-Clinical Factors version. The number of lifetime hospitalizations and the survival days (defined as the number of days between the last discharge and the most current readmission for all patients who had been readmitted to the hospital) were calculated. Results: The prevalence of nicotine use disorder among bipolar patients was 22.3 (n = 27). Male gender was the only demographic factor that was statistically associated with nicotine use disorder (p < .001). Patients with nicotine use disorder had significantly more psychiatric hospitalizations than those without nicotine use disorder after adjusting for gender, race, employment status, education level and duration of illness (p < .001). Conclusions: The rate of nicotine use disorder among bipolar patients in this study is similar to that of the general population in Malaysia but lower than that of hospitalized bipolar patients in other parts of the world. Male bipolar patients had higher risk of nicotine use disorder, which was also associated with a higher rate of prior psychiatric hospitalizations. Because there is a high prevalence of nicotine use disorder among bipolar patients, as well as potential interactions with the course of the disorder, nicotine use should be addressed in these patients. (Journal of Dual Diagnosis, 8:28-34, 2012)